Government Expenditure, Manufacturing Growth, C02 emission: A Causality Analysis in Malaysia - Samah, Irza Hanie Abu; Abd Rashid, Intan Maizura; Husain, Wan Ahmad Fauzi Wan; lskandar, Shah; Abdullah, Muhammad Fazlee Sham; Amlus, Mohammad Harith (International Journal of Energy Economics and Policy, 2020)
The main objective of the study is to explore government expenditure, C02 emission and manufacturing output in one model. These comprehensive literature reviews related to this topic of interest prove evidence upon variations towards the causality relationship that exists between government expenditure, C02 emission and manufacturing output. Most of past literatures had studied on the relationship of these variables, however separately. This study is done in order to test the relationship between government expenditure. C02 emission and manufacturing output on pollution in Malaysia. The data is secondarily obtained from The World Bank, The Eurostat, The European Environment Agency (EEA) and the international Monetary Fund (IMF) on the basis of a 39 of data collection from 2005 to 2019. The amounts of government expenditure, C02 emission and manufactu1ing output are then valued from the data usable. The study aims to analyses to whether or not do the variables hold causal to each other. This study discusses on the impacts of economic sectors on pollution the government expenditure, C02 emission and manufacturing consumption as its variables. Upon examining the study, an annual time series data covering the period of 2005 to 2019 in Malaysia were used. Models such as Augmented Dickey - Fuller (ADF) unit root test, Johansen and Juselius (1990) Co- Integration test, Vector Error Correction Model test and Granger Causality test were employed, each its own purposes. The conclusion on the findings limitation of the studies and suggestion for future references will later on be discussed in this chapter. Keywords: environmental pollution, air emission, C02 emission, Economic Growth, Malaysia JEL Classifications: E31, Q41, O11 DOI: https://doi.org/10.32479/ijeep.9766